Forms of adaptation of coffee producers to the market liberalization: proposal of an analytical typology from a case study in the Matas de Minas region - Singulano, Marisa Alice; Salej Higgins, Sílvio (Programa de Pós-graduação em Desenvolvimento, Agricultura e Sociedade da Universidade Federal Rural do Rio de Janeiro (CPDA/UFRRJ), 2021)
The article addresses the forms of adaptation that coffee farmers adopt to the context of market liberalization. We analyze how coffee growers build their strategies for adapting to the new context and the relationship of these strategies with the reconfiguration of forms of market control. A case study was carried out in the Matas de Minas region, typically an area of ​​family production, considering the post-1990 period, being a region still little considered in the literature. Based on the qualitative data obtained through the research, we propose an analytical model focused on the construction of a typology of producers, which aims to describe the diversity of ways of adapting to the new economic and institutional context defined by liberalization. The analysis is based on the neoinstitutional perspective of economic sociology, focusing on the processes of social construction of market strategies and structures, in this case guided, fundamentally, by the issue of the social construction of quality. This analytical proposal is opposed to the perspective of transaction cost economics, the main model to guide studies on agro-industrial or agri-food systems in Brazil today, offering a theoretical and methodological alternative.